2016
DOI: 10.18270/cuaderlam.v12i22.1785
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de riesgo financiero para una Entidad Sin Ánimo de Lucro (ESAL) dedicada a proyectos de mejoramiento de vivienda rural en Cundinamarca, Colombia

Abstract: En el presente texto se exponen consideraciones de viabilidad y riesgo financiero de una Entidad Sin Ánimo de Lucro (ESAL) que se dedicará a promocionar proyectos que mejoren condiciones de vivienda rural, en el departamento de Cundinamarca en Colombia. Se adelanta un análisis de riesgo financiero que simula el tiempo y costo de ejecución de un proyecto de mejoramiento de vivienda mediante la dinámica de sistemas. Los resultados inicialmente obtenidos garantizan un flujo de caja positivo para sus primeros cinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Likely, there was a chance of 75% that the project's Internal Rate of Return would be between 60% and 75%. Hence, these results match with the findings of [12][13][14][15]. Those studies found that water and sanitization projects had a good chance of being sustainable and beneficial to the population correctly.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Likely, there was a chance of 75% that the project's Internal Rate of Return would be between 60% and 75%. Hence, these results match with the findings of [12][13][14][15]. Those studies found that water and sanitization projects had a good chance of being sustainable and beneficial to the population correctly.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the project's Internal Rate of Return, only former users benefit, and population growth positively impacts production. Then, those results do not match with the results of [12,14,15] because those studies stated that other factors impacted the Internal Rate of Return. The differences might be related to how the previous studies analyzed the financial information about their projects.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations